(untitled) (Physical Education, Health and Social Sciences, 2025)
A malignant brain tumor with a dismal prognosis and few available treatments is glioblastoma multiforme (GBM). The blood-brain barrier (BBB) poses challenges for therapeutic agents reaching the tumor site. Lipid-based nanoparticles (LBNPs) have emerged as a promising solution to get better outcomes in GBM therapy. LBNPs include liposomes, lipid nanoparticles (LNP), solid lipid nanoparticles (SLPs), lipid Nano emulsion (LNE), and nanostructured lipid carrier (NLC). The compromised BBB restricts the amount of medication that can flow through it and prevents it from reaching the tumor location. This review discusses the status of LNPs in GBM treatment, their types, and mechanisms of action, advantages and challenges, including toxicity, reproducibility and targeting ability. The review also explores the combination of LNPs with radiation therapy and immunotherapy to enhance therapy results.